2017
DOI: 10.1093/mnras/stx1951
|View full text |Cite
|
Sign up to set email alerts
|

Scattering-produced (sub)millimetre polarization in inclined discs: optical depth effects, near–far side asymmetry and dust settling

Abstract: Disk polarization at (sub)millimeter wavelengths is being revolutionized by ALMA observationally, but its origin remains uncertain. Dust scattering was recently recognized as a potential contributor to polarization, although its basic properties have yet to be thoroughly explored. Here, we quantify the effects of optical depth on the scattering-induced polarization in inclined disks through a combination of analytical illustration, approximate semi-analytical modeling using formal solution to the radiative tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
126
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(152 citation statements)
references
References 41 publications
25
126
1
Order By: Relevance
“…This is the result of a slight azimuthal curvature in the polarization orientations furthest from the disk center (along the major axis), seen in the top panel of Figure 1. This is consistent with the pure-scattering models of Yang et al (2016aYang et al ( , 2017, as well as with the morphology of the polarization in the 870 μm observations of HLTau reported in Stephens et al (2017). Note, however, that while the slight azimuthal curvature can be explained by pure self-scattering, it could also be due to the superposition of polarized emission both from self-scattering and from dust grains aligned with the dust emission gradient (Tazaki et al 2017).…”
Section: Distribution Of Polarization Angles Across the Imlup Disksupporting
confidence: 89%
See 1 more Smart Citation
“…This is the result of a slight azimuthal curvature in the polarization orientations furthest from the disk center (along the major axis), seen in the top panel of Figure 1. This is consistent with the pure-scattering models of Yang et al (2016aYang et al ( , 2017, as well as with the morphology of the polarization in the 870 μm observations of HLTau reported in Stephens et al (2017). Note, however, that while the slight azimuthal curvature can be explained by pure self-scattering, it could also be due to the superposition of polarized emission both from self-scattering and from dust grains aligned with the dust emission gradient (Tazaki et al 2017).…”
Section: Distribution Of Polarization Angles Across the Imlup Disksupporting
confidence: 89%
“…Dust settling can be constrained with scattering models (e.g., Kataoka et al 2015;Yang et al 2017). Yang et al (2017) have shown that, in inclined disks such as IMLup, the near side of the disk would be significantly brighter in polarized intensity than the far side if the disk were optically thick (i.e., τ ⊥ > 1) and the grains responsible for the scattering-induced polarization had a significant vertical extent.…”
Section: Constraining Dust Settling In Imlupmentioning
confidence: 99%
“…Depolarization can also occur due to high optical depth (see Figure3 of Yang et al 2017), but this is not likely the case here since the optical depth is expected to be low along this depolarization strip: τ∼0.08 even at the highest contour level assuming T=30 K.…”
Section: Figure10(d) Ofmentioning
confidence: 95%
“…More recently, it has been demonstrated that very large (a > 10 µm) dust grains are able to produce polarisation by scattering thermal dust emission, a process that is called 'self-scattering'. This was first predicted to be observable in protoplanetary disks (Kataoka et al 2015) and then confirmed by numerous ALMA observations (Kataoka et al 2016;Yang et al 2017;Girart et al 2018). B-BOP, with its 100 µm polarised channel, would be able to detect and characterise the spectral dependence of polarisation by scattering due to ∼15 µm dust grains (Kataoka et al 2015), if present.…”
Section: Towards a Tentative Detection Of Polarisation By Dust Self-smentioning
confidence: 70%